Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/ee9.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Associations between PFAS occurrence and multimorbidity as observed in an electronic health record cohort

Abstract: Background: Per and polyfluoroalkyl substances (PFAS) are associated with health outcomes ranging from cancer to high cholesterol. However, there has been little examination of how PFAS exposure might impact the development of multiple chronic diseases, known as multimorbidity. Here, we associated the presence of one or more PFAS in water systems serving the zip code of residence with chronic disease and multimorbidity. Methods: We used data from the unregulated contaminant monitoring rule 3 to estimate expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The results reported here are consistent with a previous study in North Carolina based on electronic health records (Ward-Caviness, Moyer et al 2022). That study also reported similar associations between presence of any PFAS detected in the drinking water system with hypertension (OR 1.32 (1.15, 1.52)) and chronic kidney disease (OR 1.14 (0.87, 1.51)).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results reported here are consistent with a previous study in North Carolina based on electronic health records (Ward-Caviness, Moyer et al 2022). That study also reported similar associations between presence of any PFAS detected in the drinking water system with hypertension (OR 1.32 (1.15, 1.52)) and chronic kidney disease (OR 1.14 (0.87, 1.51)).…”
Section: Discussionsupporting
confidence: 93%
“…Cardiovascular disease has been linked to PFAS by experimental and epidemiologic studies (Meneguzzi, Fava et al 2021) (Meneguzzi, Fava et al 2021, Wen, Wang et al 2022). Hypertension and dyslipidemia have been linked to serum PFAS among Norwegian adolescents (Averina, Brox et al 2021), US women (Ding, Karvonen-Gutierrez et al 2022) and adolescents (Ma, Xu et al 2019), and to PFAS drinking water contamination among North Carolina adults (Ward-Caviness, Moyer et al 2022). Preeclampsia, acute onset hypertension in pregnant women, and other reproductive related outcomes were found to be associated with PFAS in two large systematic reviews (Gao, Ni et al 2021, Rickard, Rizvi et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ecological study conducted in North Carolina (United States, 10 168 participants) showed that exposure to PFOA, PFHxS, and PFOS in drinking water was associated with the risk of hypertension. 91 Analyses of populations in the contaminated Veneto Region (Italy) showed that PFOA, PFNA, PFHxS, and PFOS are associated with hypertension. 81,82 Consistent with the analyses of blood pressure, analyses of NHANES cohorts showed that PFOA, PFNA, and PFOS are associated with hypertension risk.…”
Section: Blood Pressure and Hypertensionmentioning
confidence: 99%
“…A survey of the US general population (NHANES, 2003-2014; 8948 participants) showed that PFOA, PFNA, PFHxS, and PFOS serum concentrations correlated with total serum cholesterol and LDL-C. 104 PFOA and PFHxS concentrations also were linked with HDL-C. 104 An ecological study of people living in a contaminated region of North Carolina, USA (10 168 participants), reported that exposure to PFAS (PFOA, PFOS, and PFHxS) in drinking water was associated with an increased risk of dyslipidemia. 91 Additional analyses of people living in North Carolina (49 and 326 participants) exposed to contaminated drinking water showed that PFOA, PFNA, PFHxS, and PFOS (but not PFDA) were associated with higher total serum cholesterol and non-HDL-C. 105,106 Analyses of participants in the Pounds Lost study (United States, 326 participants) demonstrated that PFOA was associated with higher serum ApoB (apolipoprotein B) and ApoC-III (apolipoprotein C-III), PFDA was linked with higher intermediate-density lipoprotein cholesterol+LDL-C+ApoC-III, and PFHxS was associated with higher HDL-C+ApoC-III; no associations were reported for PFNA or PFOS. 107 Along similar lines, analysis of the general Canadian population (CHMS [2007-2009, 2009-2011, and 2016-2017], 6045 participants) showed that PFOA, PFDA, PFHxS, and PFOS were all associated with higher total cholesterol.…”
Section: Dyslipidemia and Atherosclerosismentioning
confidence: 99%